Little critter's the trip - Mayer, Mercer, 1943- (New York : Golden Book, 1988)
During their car trip to Lake Wakatookee, the Critter family introduces the letters from A to Z.
"A Golden easy reader"--Cover.
Col. ill. on lining papers.
Keywords: Travel -- Fiction; Family life -- Fiction; Alphabet